Evidence of Bacterial Biofilms among Infected and Hypertrophied Tonsils in Correlation with the Microbiology, Histopathology, and Clinical Symptoms of Tonsillar Diseases - Alasil, S.M.; Omar, R.; Ismail, S.; Yusof, M.Y.; Dhabaan, G.N.; Abdulla, M.A. (Hindawi Publishing Corporation, 2013)
Diseases of the tonsils are becoming more resistant to antibiotics due to the persistence of bacteria through the formation of biofilms. Therefore, understanding the microbiology and pathophysiology of such diseases represent an important step in the management of biofilm-related infections. We have isolated the microorganisms, evaluated their antimicrobial susceptibility, and detected the presence of bacterial biofilms in tonsillar specimens in correlation with the clinical manifestations of tonsillar diseases. Therefore, a total of 140 palatine tonsils were collected from 70 patients undergoing tonsillectomy at University Malaya Medical Centre. The most recovered isolate was Staphylococcus aureus (39.65%) followed by Haemophilus influenzae (18.53%). There was high susceptibility against all selected antibiotics except for cotrimoxazole. Bacterial biofilms were detected in 60% of patients and a significant percentage of patients demonstrated infection manifestation rather than obstruction. In addition, an association between clinical symptoms like snore, apnea, nasal obstruction, and tonsillar hypertrophy was found to be related to the microbiology of tonsils particularly to the presence of biofilms. In conclusion, evidence of biofilms in tonsils in correlation with the demonstrated clinical symptoms explains the recalcitrant nature of tonsillar diseases and highlights the importance of biofilm’s early detection and prevention towards better therapeutic management of biofilm-related infections.